Electrospun Poly (Vinyl Alcohol) (PVA) fiber mats as carriers for extract from agarwood branch - Mohd Noor, Najihah; Hashim, Yumi Zuhanis Has-Yun; Ahmad Nor, Yusilawati; Tshai, Albert; Wan Salim, Wan Wardatul Amani; Sopyan, Iis (nternational Institute for Halal research and Training (INHART), International Islamic University Malaysia (IIUM), 2018)
In this paper, electrospinning was carried out to determine the optimum level for selected process parameters that produce poly (vinyl alcohol) (PVA) loaded agarwood branch ethanolic extract (ABEE) fiber mat which is potentially useful for wound healing application. The process parameters to optimize the fabrication of ABEE-loaded PVA fiber mats were studied using One-Factor-at-a-Time (OFAT). The parameters include voltage supply (kV), flow rate (ml/h) and collection distance (cm). The optimal molecular weight of PVA for the preparation of smooth and beadless PVA nanofiber in this study was 145,000 g/mol. The diameter of the electrospun of both PVA neat and ABEE-loaded PVA fiber mats were 312.2 nm and 431.2 nm; respectively with the formation of smooth fibers with minimum beadings. Based on the OFAT method, the optimal process parameters for fabrication of PVA/ABEE fiber mats were spinned at the voltage of 20 kV, flow rate of 0.7 ml/h and collection distance of 14 cm. The agarwood extract incorporated-fiber mats could be further developed into alternative halal transdermal patches for wound healing.